MASYARAKAT EKONOMI ASEAN (MEA) DAN PENOLAKAN TERHADAP SWASTANISASI AIR (Jurnal Hukum Mimbar Justitia, 2016)
UUD 1945 as the basic constitution has mandated that natural resources shouldbe controlled by the state for the welfare of citizen, even in Islam point of view,water is public rights property to human welfare. The provisions are bindingunder any circumstances. Meanwhile, the issue of MEA has opened the horizonand paradigm in economy, especially, in the regulation of natural resources,specifically water, that has weak regulation access, and opened the privatizationof water so that the exploitation on a large scale by foreign companies whichcome to Indonesia